2011
DOI: 10.1128/aem.02229-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of an O-Antigen Serotyping Scheme for Cronobacter sakazakii

Abstract: Cronobacter sakazakii is an opportunistic pathogen that can cause severe infections. Serotyping provides a basis for the categorization of bacterial strains and is an important tool for epidemiological and surveillance purposes. In this study, of the 135 Cronobacter strains tested initially, 119 were identified as C. sakazakii and used. A serotyping scheme for C. sakazakii that classifies strains based on their different O antigens was developed. Seven antisera that exhibited high agglutinin titers (>640) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…Based on this approach, the first two O-antigen serotypes were characterized, and denoted as O1 and O2. More recently, Sun et al (2011) added five additional C. sakazakii O-antigen serotypes that correlated with the PCR-RFLP profiles. Jarvis et al (2011) extended the original Mullane molecular characterization scheme to include other Cronobacter spp.…”
Section: Molecular O-antigen Typingmentioning
confidence: 99%
“…Based on this approach, the first two O-antigen serotypes were characterized, and denoted as O1 and O2. More recently, Sun et al (2011) added five additional C. sakazakii O-antigen serotypes that correlated with the PCR-RFLP profiles. Jarvis et al (2011) extended the original Mullane molecular characterization scheme to include other Cronobacter spp.…”
Section: Molecular O-antigen Typingmentioning
confidence: 99%
“…In a recent study, serological typing was used to identify five additional C. sakazakii serotypes, bringing the total number of serotypes for this species to seven (42). Other information available about Cronobacter O antigens comes from chemical characterization studies that have identified the repeat polysaccharide sugar composition of five C. sakazakii isolates, one C. malonaticus isolate, and one C. muytjensii isolate (1,2,7,(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Research on the organism has considerably progressed in recent years, with improved isolation, identification, and molecular typing methods (22,38,40). These methods have detected considerable diversity within the genus, warranting further detailed investigation.…”
mentioning
confidence: 99%